Pelatihan Penyusunan Laporan Keuangan Homestay Berbasis Excel di Desa Wisata Pinge Desa Baru Kecamatan Marga Kabupaten Tabanan - Ni Ketut Mareni; I Wayan Tuwi (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2023)
The Hospitality Accounting Management Study Program, one of the study programs at the Bali Tourism Polytechnic, carries out community service activities in Pinge Tourism Village, Baru Village, Tabanan 16 to 17 September 2022. The form of community service activity for the Hospitality Accounting Management Study Program in Pinge Tourism Village is The training with the theme "Training on the Preparation of an Excel-Based Accounting Information System in Pinge Tourism Village". This activity was attended by 30 participants who are owners and managers of homestays in Pinge Tourism Village, Baru Village. The Community Service Hospitality Accounting Management Study Program was held for 13 hours, starting with a presentation on the management of the Pinge Tourism Village, determining room selling prices and homestay operational costs, and continued with training on preparing financial reports using the Excel application. Participants' assessment of the Community Service activities of the Hospitality Accounting Management Study Program was that most participants considered the material very relevant to their needs. All participants stated that after participating in all activities they felt they had gained additional knowledge, insight, and skills in making homestay financial reports.